Oregano essential oil: Effect on sensory acceptability - Cattelan, Marília Gonçalves [UNESP] (2015)
Purpose – This paper aimed to evaluate sensory acceptability of salad dressing formulated with different quantities of oregano essential oil (OEO) and salt as a starting point for the use of the spice as a natural preservative in food. Design/methodology/approach – Sensory assessment of salad dressing with OEO was evaluated in relation to the following attributes: appearance, aroma, consistence, flavour and overall acceptability. Five formulations were developed with variation in the levels of OEO and sodium chloride through a 22 factorial design with a central point. A nine-point hedonic scale was used, besides purchase intent by a structured five-point scale. Findings – There was no significant difference in the acceptance of the samples. Cluster analysis showed that formulation with intermediate quantities of salt and OEO was preferred by the consumers. OEO salad dressings with low salt content, regardless of OEO amount, presented higher intention to purchase. Research limitations/implications – Due to an increasing interest in the use of natural preservatives to replace chemical additives, this study provided a starting point for further investigations concerning sensory acceptability of OEO in food. Practical implications – Finding the balance between pleasant flavour and significant reduction of the use of salt in foods for dietary reasons is a complex challenge. Furthermore, studies need to be performed concerning interaction between amounts of essential oils and salt. Originality/value – This study provides insights that suggest a promising usage of OEO in food.